Regional features of forestry climate adaptation - Sinkevich Sergei (BIO Web of Conferences)
A set of measures designed to mitigate and prevent the possible climate change impacts on forestry in the Karelian boreal forest region is proposed based on the analysis of climate dynamics in the study area, the species and age structure of forests and their designated use. The carbon balance was estimated for the forestry fund of ten central forest administrate districts differing in the tree species composition, productivity, and major designated use. Age-related patterns of carbon accumulation in stands formed by major tree species are demonstrated. The article substantiates the importance of tailoring regional carbon balance planning to the specific features of the territory and of applying an integrated approach to the assessment of the ecological potential of forests.